Cell entry of bovine respiratory syncytial virus through clathrin-mediated endocytosis is regulated by PI3K-Akt and Src-JNK pathways - Liu, Yang; Yang, Dongliang; Jiang, Wen; Chi, Tianying; Kang, Jingli; Wang, Zhiliang; Wu, Faxing (Frontiers in Microbiology, 2024)
Bovine respiratory syncytial virus (BRSV) is an RNA virus with envelope that causes acute, febrile, and highly infectious respiratory diseases in cattle. However, the manner and mechanism of BRSV entry into cells remain unclear. In this study, we aimed to explore the entry manner of BRSV into MDBK cells and its regulatory mechanism. Phenotpyc approach indicate that BRSV enters MDBK cells through endocytosis, relying on dynamin, specifically via clathrin-mediated endocytosis rather than caveolin-mediated endocytosis and macropinocytosis. We observed that the entered BRSV initially localizes in early endosomes and subsequently localizes in late endosomes. Additionally, our results of western blot, virus titer and virus copies demonstrate that BRSV entry through clathrin-mediated endocytosis is regulated by PI3K-Akt and Src-JNK signaling pathways. Overall, our study suggests that BRSV enters MDBK cells through clathrin-mediated endocytosis, entered BRSV is trafficked to late endosome via early endosome, BRSV entry through clathrin-mediated endocytosis is regulated by PI3K-Akt and Src-JNK signaling pathways.